Unbounded solutions of BVP for second order ODE with p-Laplacian on the half line - Liu, Yuji (2013)
By applying the Leggett-Williams fixed point theorem in a suitably constructed cone, we obtain the existence of at least three unbounded positive solutions for a boundary value problem on the half line. Our result improves and complements some of the work in the literature.